2022
DOI: 10.48550/arxiv.2203.09776
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

VO2 Does Not Host a Photoinduced Long-lived Monoclinic Metallic Phase

Abstract: Femtosecond laser pulses can trigger phase transitions and sometimes even achieve transient nonequilibrium states that are not accessible in equilibrium. Vanadium dioxide (VO2) exhibits a first-order insulator-to-metal transition accompanied by a monoclinic-to-rutile structural transition near room temperature. Recently there is extensive debate over whether VO2 hosts a transient long-lived monoclinic metallic phase with femtosecond photoexcitation. We developed a new method to synthesize quasi-single-crystal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…The similar thresholds of electronic excitation for both SPT and IMT revealed here are consistent with the experimental measurements carefully characterizing the heating effects where a single threshold is observed for both SPT and IMT (26). A recent experimental work also demonstrated only one threshold for both the superstructure and nonsuperstructure peaks via well-separated diffraction spots of quasi-single-crystal VO 2 (40). Thus, both ultrafast SPT and IMT of VO 2 can be triggered with the same laser pulses, indicating the same fluence thresholds in experiments.…”
Section: Photoinduced Isostructural Imtsupporting
confidence: 89%
“…The similar thresholds of electronic excitation for both SPT and IMT revealed here are consistent with the experimental measurements carefully characterizing the heating effects where a single threshold is observed for both SPT and IMT (26). A recent experimental work also demonstrated only one threshold for both the superstructure and nonsuperstructure peaks via well-separated diffraction spots of quasi-single-crystal VO 2 (40). Thus, both ultrafast SPT and IMT of VO 2 can be triggered with the same laser pulses, indicating the same fluence thresholds in experiments.…”
Section: Photoinduced Isostructural Imtsupporting
confidence: 89%
“…Furthermore, with newly synthesized quasi-single-crystal freestanding VO 2 films and high resolution mega-electron-volt ultrafast electron diffraction, Xu et al measured the photoinduced evolution of the diffraction intensity in the momentum space and their results indicated no evidence for the transient monoclinic metallic phase. [154] These studies suggested against the existence of a decoupled structural and electronic phase transition. On the other hand, Johnson et al measured the spacial evolution of VO 2 thin films with nano-scale resolution after excitation by using time-and spectrally-resolved coherent X-ray imaging.…”
Section: Photoinduced Insulator-metal Phase Transitionsmentioning
confidence: 99%